Effect of cast rectifiers on the marginal fit of UCLA abutments - Ana Paula Gumieiro Jaime; Diego Klee de Vasconcellos; Alfredo Mikail Melo Mesquita; Estevão Tomomitsu Kimpara; Marco Antonio Bottino (Journal of Applied Oral Science, 2007)
OBJECTIVES: This study assessed the effect of cast rectifiers on the marginal misfit of cast UCLA abutments compared to premachined UCLA abutments. The influence of casting and porcelain baking on the marginal misfit of these components was also investigated. METHODS: Two groups were analyzed: test group - 10 cast UCLA abutments, finished with cast rectifier and submitted to ceramic application; control group - 10 premachined UCLA abutments, cast with noble metal alloy and submitted to ceramic application. Vertical misfit measurements were performed under light microscopy. In the test group, measurements were performed before and after the use of cast rectifiers, and after ceramic application. In the control group, measurements were performed before and after casting, and after ceramic application. Data were submitted to statistical analysis by ANOVA and Tukey's test (a= 5%). RESULTS: The use of cast rectifiers significantly reduced the marginal misfit of cast UCLA abutments (from 25.68mm to 14.83mm; p<0.05). After ceramic application, the rectified cylinders presented misfit values (16.18mm) similar to those of premachined components (14.3 mm). Casting of the premachined UCLA abutments altered the marginal misfit of these components (from 9.63 mm to 14.6 mm; p<0.05). There were no significant changes after porcelain baking, in both groups. CONCLUSION: The use of cast rectifiers reduced the vertical misfit of cast UCLA abutments. Even with carefully performed laboratory steps, changes at the implant interface of premachined UCLA abutments occurred. Ceramic application did not alter the marginal misfit values of UCLA abutments.